The Relationship Between Emotional Intelligence and Students' Self-Adjustment At SMK Negeri 2 Malang - A.Taufiq Hidayat; Sudrajad, wahyu (Jurusan Tarbiyah dan Pendidikan, 2025)
This study examines the relationship between emotional intelligence and self-adjustment among tenth-grade students at once SMK Negeri in East Java. Using a quantitative approach, data were collected through questionnaires and analyzed using Pearson's Product Moment correlation. The findings indicate that most students possess a good level of emotional intelligence, with 80% categorized as having good emotional intelligence and 10% classified as very good. Similarly, self-adjustment levels were also predominantly good, with 70% of students demonstrating good self-adjustment skills. The statistical analysis revealed a significant positive correlation (r = 0.990) between emotional intelligence and self-adjustment, indicating that students with higher emotional intelligence tend to adjust better to their environment. This study aligns with previous research, reinforcing the importance of fostering emotional intelligence in educational settings. Schools and educators should integrate emotional intelligence development programs to enhance students’ adaptability, social relationships, and overall well-being.